Detecting and Preventing Cyber Attacks on Local Area Networks : A Working Example - TINIŞIK, Umut AL; YILDIZ, Sezer (International Journal of Computer Sciences and Engineering, 2018)
To ensure secure communication on the network, the principles of confidentiality, integrity and accessibility must be carried out in unity. To prevent external attacks on the network, many threats are eliminated by using firewalls between the external network and the internal network. However, different security scenarios need to be implemented against threats that may come from within the local area networks. For this reason, the factors that may cause security vulnerabilities in the internal network should be checked and the security should be considered. One of the most important problems encountered here is the unnecessary network traffic that occurs in internal networks, slowing the system and making it inoperable. In this article, using the GNS3 (Graphical Network Simulator) network simulation program, MAC (Media Access Control) flood, DHCP (Dynamic Host Configuration Protocol) starvation and spoofing and Arp (Address Resolution Protocol) poisoning attacks are detected and a working example has been carried out to prevent it